1987
DOI: 10.1128/jb.169.1.26-32.1987
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of heat shock, SOS, and oxidation stress regulons and accumulation of nucleotides in Escherichia coli

Abstract: Heat and various inhibitory chemicals were tested in Escherichia coli for the ability to cause accumulationi of adenylylated nucleotides and to induce proteins of the heat shock (htpR-controlled), the oxidation stress (oxyR-controlled), and the SOS (lexA-controlled) regdlons. Under the conditions used, heat and ethanol initiated solely a heat shock response, hydrogen peroxide and 6-amino7-chloro-5,8-dioxoquinoline (ACDQ) induced primarily an oxidation stress response and secondaily an SOS response, nalidixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
314
1
5

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 485 publications
(335 citation statements)
references
References 28 publications
15
314
1
5
Order By: Relevance
“…enterocolitica. In E. coli, there is a set of 17 heat shock proteins, one of which is the GroEL protein (Neidhardt et al, 1984;VanBogelen et al, 1987). The fact that CRPA is found in the same relative migratory position in two-dimensional gels as the GroEL protein of E. coli, coupled with the fact that the native molecular mass of both proteins is > 500 kDa, suggested to us that they might be similar or identical proteins (Hendrix, 1979).…”
Section: Species Specificity Of Crpa Mabsmentioning
confidence: 99%
“…enterocolitica. In E. coli, there is a set of 17 heat shock proteins, one of which is the GroEL protein (Neidhardt et al, 1984;VanBogelen et al, 1987). The fact that CRPA is found in the same relative migratory position in two-dimensional gels as the GroEL protein of E. coli, coupled with the fact that the native molecular mass of both proteins is > 500 kDa, suggested to us that they might be similar or identical proteins (Hendrix, 1979).…”
Section: Species Specificity Of Crpa Mabsmentioning
confidence: 99%
“…5 in SI Appendix). Similar concentrations of H 2 O 2 , for instance, have been used in earlier proteomic studies designed to investigate the E. coli oxidative stress response (28). To detect proteins that are rapidly oxidatively modified in vivo, we then harvested cells 10 min after addition of the oxidants and conducted our OxICAT thiol trapping experiments.…”
Section: Oxicat Provides a Quantitative Assessment Of The Cellular Redoxmentioning
confidence: 99%
“…The genes induced by H202 include katG, ahpC, ahpF and gorA, and are all controlled by the positive regulator OxyR (Christman et al, 1985(Christman et al, , 1989Morgan et al, 1986). The so-called soxR and oxyR regulons seem to overlap other stress response regulons such as that for heat-shock, since some proteins are induced in common by different stresses (Greenberg & Demple, 1989;VanBogelen et al, 1987), and some cross-protection has been observed (Christman et al, 1985;Jenkins et al, 1988).…”
Section: Introductionmentioning
confidence: 99%